HEAD OF HOUSEHOLD BEHAVIOR REGARDING THE ERADICATION OF DENGUE FEVER MOSQUITO NESTS IN LAMPAGEU VILLAGE, PEUKAN BADA SUBDISTRICT, ACEH BESAR REGENCY - Lensoni; Zahara, Hafni; Yanti, Susi; Zikra, Safaratul; Makhgirah, Nadilatul; Safira, Safra; Khatimah, Husnul; Indy, Elsa (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
The "3M Plus" mosquito nest eradication movement has proven highly effective in preventing dengue disease and promoting environmental hygiene and healthy living behaviors. This study aims to explore the relationship between household head behavior and the implementation of dengue fever mosquito nest eradication. Using a descriptive analytic approach with a cross-sectional study design and simple random sampling, the research involved 14 family heads as participants. Data were collected through interviews using a questionnaire and supplemented with observational data. Data processing encompassed editing, coding, and tabulating, followed by bivariate analysis (Chi-square test) and multivariate analysis (Binary Logistic Regression) at a 95% confidence interval. The results indicate a significant correlation between attitudes (p=0.000) and the role of community leaders (p=0.039) in the eradication of dengue mosquito nests. However, no relationship was observed between knowledge (p=0.767) and mosquito nest eradication. Attitude emerged as the dominant predictor (Exp (B) = 7.2) for its association with the implementation of eradication efforts. This research highlights the importance of positive attitudes and the role of community leaders in effectively eradicating dengue mosquito nests, ultimately contributing to the success of such efforts in Peukan District, Aceh Besar Regency.